THE USE OF SYNONYMS IN SAID AHMAD'S WORK "SILENCE" - Bazarova Dildor; Ro‘ziyeva Ozoda (Bright Mind Publishing, 2025)
This article analyzes the lexical, semantic and methodological features of synonyms and highlights the possibilities of their expression in the literary text. The study was based on Said Ahmad's work "Silence" and analyzed semantically the synonymous lines of time, condition, personality and attitude. It is based on the fact that the contextual use of synonyms increases the objectivity and emotional impact of the text, and provides methodological richness.
Keywords: Synonymy, lexical synonyms, stylistic tool, literary text, semantic analysis, methodology, work